Direct intra-accumbal infusion of a beta-adrenergic receptor antagonist abolishes WIN 55,212-2-induced aversion - Carvalho, Ana Raquel Franky Gomes (2011)
The cannabinoid system is known to interact with a variety of neuromodulators in the central nervous system and impacts diverse behaviors. Previous studies have demonstrated that limbic norepinephrine is a critical determinant in the behavioral expression of cannabinoid-induced aversion. The present study was carried out to define the adrenergic receptor subtype involved in mediating cannabinoid-induced behavioral responses. An acute microinjection of the 1-adrenergic receptor blocker, betaxolol, directly into the nucleus accumbens (Acb), was able to prevent WIN 55,212-2-induced aversion, but not lithium-induced aversion, as measured in a place conditioning paradigm. These results suggest that noradrenergic transmission in the Acb is important for cannabinoid-induced aversion and that beta-adrenergic antagonists may be effective in counteracting negative side effects of cannabinoid-based agents.